2016
DOI: 10.14392/asaa.2016090206
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Professional Accountants' Cognitive Reflection Ability

Abstract: In this paper, we map Brazilian professional accountants' cognitive reflection abilities, exploring the demographic characteristics associated with such ability. To operationalize individuals' cognitive reflection ability, we use the Cognitive Reflection Test (CRT). Our sample consists of 4,902 Brazilian accountants who voluntarily answered an online survey. We analyze data using three ordered logistic regression (ologit) models that provide a good fit for our data set. Our exploratory analysis reveals that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Turning to numeracy, deductive reasoning and cognitive reflection, we found that, in line with research into fluid intelligence (Tucker-Drob, 2011) and other cognitive abilities (Portugal Barcellos et al, 2016), younger voters outperformed older voters. With respect to cognitive biases, we found that younger voters were less susceptible to Dunning-Kruger and ideologically motivated reasoning than older voters.…”
Section: Discussionsupporting
confidence: 81%
“…Turning to numeracy, deductive reasoning and cognitive reflection, we found that, in line with research into fluid intelligence (Tucker-Drob, 2011) and other cognitive abilities (Portugal Barcellos et al, 2016), younger voters outperformed older voters. With respect to cognitive biases, we found that younger voters were less susceptible to Dunning-Kruger and ideologically motivated reasoning than older voters.…”
Section: Discussionsupporting
confidence: 81%
“…As a result, it can be stated that the current sample contains neither too many impulsive, nor too many reflective participants, since it contains more reflective participants compared to studies by Frederick (2005), Toplak et al (2011), andViator et al (2014), but more impulsive participants compared to those by Oechssler et al (2009), Hoppe andKusterer (2011), Alós-Ferrer andHügelschäfer (2016) and Barcellos et al (2016).…”
Section: Sample Representativenessmentioning
confidence: 90%
“…On the other hand, the current sample contains more impulsive participants compared to the samples surveyed by other studies, such as those by Oechssler et al (2009), Hoppe andKusterer (2011), andAlós-Ferrer andHügelschäfer (2016), who analyzed samples comprised of students who were given financial compensation (varying from EUR 0.20-5.00 per correct answer). In addition, the current sample contains more impulsive participants compared to that surveyed by Barcellos et al (2016), who did not offer any compensation to participants (their sample of 4,902 accountants in Brazil was comprised of preparers, auditors, and analysts of financial reports, as well as managers and professors). Note that Barcellos et al (2016, p. 235) identified that "auditors presented the highest average CRT score followed by managers, professors, analysts and preparers," which may explain why the current sample (comprised of analysts only) contains more impulsive participants compared to their sample.…”
Section: Sample Representativenessmentioning
confidence: 99%